Un implemento disenado para ayudar en la cosecha de la yuca - Díaz Durán, Alfonso (International Center for Tropical Agriculture, 1978)
A cassava root harvesting aid was designed that can be attached to a tractor with a hydraulic system. This implement breaks up the soil and loosens the roots, making their manual extraction easy. The aid, as well as the method of operating it, is described and illustrated. (CIAT)